Lipases and carboxylesterases affect moth sex pheromone compounds involved in interspecific mate recognition - Arthur de Fouchier; Elise Fruitet; Rik Lievers; Peter Kuperus; Jennifer Emerson; Fred Gould; David G. Heckel; Astrid T. Groot (Nature Communications, 2023)
Abstract Moth sex pheromones are a classical model for studying sexual selection. Females typically produce a species-specific pheromone blend that attracts males. Revealing the enzymes involved in the interspecific variation in blend composition is key for understanding the evolution of these sexual communication systems. The nature of the enzymes involved in the variation of acetate esters, which are prominent compounds in moth pheromone blends, remains unclear. We identify enzymes involved in acetate degradation using two closely related moth species: Heliothis (Chloridea) subflexa and H. (C.) virescens, which have different quantities of acetate esters in their sex pheromone. Through comparative transcriptomic analyses and CRISPR/Cas9 knockouts, we show that two lipases and two esterases from H. virescens reduce the levels of pheromone acetate esters when expressed in H. subflexa females. Together, our results show that lipases and carboxylesterases are involved in tuning Lepidoptera pheromones composition.